Gastrointestinal Endoscopy Sedation and Monitoring Practices in Spain: A Nationwide Survey in the Year 2014 - Lucendo, Alfredo J.; González-Huix, Ferrán; Tenias, José M.; López-Rosés, Leopoldo; Alonso-Aguirre, Pedro; Quintero, Enrique; Muñoz-Navas, Miguel; on behalf of the Spanish Society of Digestive Diseases, the Spanish Society of Digestive Endoscopy, and the Spanish Association of Gastroenterology (Endoscopy, 2015)
Background and study aims: The introduction of new sedative agents and a desire for improved patient care have encouraged the use of sedation for gastrointestinal (GI) endoscopy over the last decade. This survey aims to provide, within Spain, national and regional data on gastroenterologists’ endoscopic sedation and monitoring practices, and on their attitudes concerning these practices.Methods: A 19-item survey covering the current practices of sedation and monitoring in GI endoscopy was electronically mailed to all members of the three nationwide scientific societies. Results: Of 2476 e-mailed questionnaires, a total of 569 (23 %) were returned, proportionally representing the structure of the Spanish health care system. Monitoring and resuscitation resources were universally available, as well as post-endoscopy recovery rooms. Endoscopy teams usually included a registered nurse (98.5 %), an auxiliary nurse (80.5 %), and other physicians (25.7 %), generally anesthesiologists. More than half of esophagogastroduodenoscopies (EGDs) are performed with the patient under sedation; in 25 % of centers, more than 95 % colonoscopies are performed with the patient sedated, but a wide variation was observed. Pre-endoscopic risk is assessed in the vast majority of procedures. Propofol is the most commonly used sedative, either alone (in 70 % of EGDs and 80 % of colonoscopies) or in combination with other drugs. Private funding of a clinic was the only predictor of a significant increase in the use of sedation; 57.7 % of the respondents stated having difficulties in implementing sedation, with the limited availability of anesthesiologists and resuscitation training for the auxiliary staff the most common complaints. Conclusions: The use of sedation during GI endoscopy in Spain varies widely but is on the increase and is more common in private practice. Propofol is the preferred sedative in all procedures.